ISLAMIC RELIGIOUS EDUCATION (PAI) MODEL AT JUNIOR HIGH SCHOOL (SMP) MUHAMMADIYAH 1 ALTERNATIVE MAGELANG CITY (MUTUAL) - Abdurrosyid Abdurrosyid (TAWASUT, 2023)
AbstractThis paper discusses the model of Islamic Religious Education in Junior High School (SMP). The researcher raised the Muhammaiyah 1 Alternative Junior High School in Magelang City (MUTUAL) as the model under study. By using the approach of observation, interviews, and analysis, the authors attempt to describe and explain the SMP MUTUAL model and the Islamic Religious Education (PAI) model that it organizes. The research is directed at the historical conditions of SMP MUTUAL, the pattern of Islamic Religious Education (PAI), the implications of the applied PAI pattern, and its development. This study obtained the main conclusion that the PAI model in SMP MUTUAL is not only a complement to the educational curriculum, but that the implementation of PAI becomes a unified curriculum, becomes the basis for strengthening the curriculum character and school character, as well as being a model or pattern characteristic of SMP MUTUAL that distinguishes it from other institutions. another education.Keywords:, Implementation, Islamic Religious Education, Model, Development, Junior High School, Mutual.